Efficient Pyrimidone-Promoted Palladium-Catalyzed Suzuki–Miyaura Cross-Coupling Reaction - Zhang, Hong-Ping; Dai, You-Zhi; Zhou, Xi; Yu, Huang (Synlett, 2012)
An efficient Pd(OAc)2/orotic acid catalytic system has been developed for Suzuki–Miyaura cross-coupling reaction of halides with aryl- and vinylboronic acids. The use of pyrimidone as ligand makes this method useful and attractive for the synthesis of stilbenes and derivative compounds. An attractive feature of this method is the tolerance of functional groups in both substrates.
Keywords: Suzuki–Miyaura cross-coupling reaction; pyrimidones; vinylboronic acids; halides; stilbenes